Increased detection of mastitis pathogens by real‐time PCR compared to bacterial culture. (21st September 2013) - Keane, O. M.; Budd, K. E.; Flynn, J.; McCoy, F.
Abstract : Rapid and accurate identification of mastitis pathogens is important for disease control. Bacterial culture and isolate identification is considered the gold standard in mastitis diagnosis but is time consuming and results in many culture‐negative samples. Identification of mastitis pathogens by PCR has been proposed as a fast and sensitive alternative to bacterial culture. The results of bacterial culture and PCR for the identification of the aetiological agent of clinical mastitis were compared. The pathogen identified by traditional culture methods was also detected by PCR in 98 per cent of cases indicating good agreement between the positive results of bacterial culture and PCR. A mastitis pathogen could not be recovered from approximately 30 per cent of samples by bacterial culture, however, an aetiological agent was identified by PCR in 79 per cent of these samples. Therefore, a mastitis pathogen was detected in significantly more milk samples by PCR than by bacterial culture (92 per cent and 70 per cent, respectively) although the clinical relevance of PCR‐positive culture‐negative results remains controversial. A mixed infection of two or more mastitis pathogens was also detected more commonly by PCR. Culture‐negative samples due to undetected Staphylococcus aureus infections were rare. The use of PCR technology may assist in rapid mastitis diagnosis, however, accurate interpretation of PCR results in the absence of bacterial culture remains problematic.